MODEL OF BUSINESS ACTIVITIESS OF MICROFINANCE INSTITUTIONS IN INDONESIA - Etty Mulyati; Kartikasari Kartikasari; Rai Mantili; Nun Harrieti (Diponegoro Law Review, 2017)
Micro Finance Institutions (LKM) as non-bank financial institutions, are growing very rapidly in Indonesia. A very large number and scope of business in villages/sub-districts and sub-districts or districts can play a role in an inclusive financial program. The existence of LKM operation much help expand employment and improve the welfare and improving the economy and productivity of the people, especially low-income communities. The problem is how to model the business activities of LKM in Indonesia. This research will use normative juridical approach method, with analytical descriptive research specification. In an effort to provide financial services, which are intended for low-income communities and do not have access to bank financial institutions. LKM can bridge the problems of micro business access to capital is needed in business development. LKM has a different character with the other financial sector businesses, because it is not solely intended for profit. LKM business activities can be done in a conventional or sharia, includes loan/financing for micro enterprises for capital needs in business development, and management of deposits in an effort to bring awareness to the community's fond of saving, besides that LKM also provide consulting services for the purpose of business development community empowerment. To provide legal certainty for the LKM service user community, LKM institutions are regulated in LKM Laws, according to the law the LKM must be a legal entity of the Cooperative or Limited Liability Company Fostering, regulating, and supervising and licensing of LKM is performed by the Financial Services Authority (OJK).